2014
DOI: 10.1039/c4ra09798j
|View full text |Cite
|
Sign up to set email alerts
|

First ligand-free, microwave-assisted, Heck cross-coupling reaction in pure water on a nucleoside – application to the synthesis of antiviral BVDU

Abstract: For the first time, a palladium catalyzed Heck cross-coupling reaction between 5-iodo-2′-deoxyuridine and various acrylate derivatives was performed using ligand-free conditions and microwave assistance in pure water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Brivudine (BVDU) is an antiviral nucleoside analog used in the treatment of herpes zoster virus (HSV-1). Hervé et al in 2014 reported the synthesis of BVDU using a Pd-catalyzed Heck alkenylation reaction in 56% yield by using 10 mol% of Pd(OAc) 2 as a catalyst [52]. With a highly active catalytic system in hand, we explored the possibility of addressing the issues related to BVDU synthesis such as lower yields and the use of a high catalyst concentration.…”
Section: Synthesis Of Antiviral Drug Brivudine (Bvdu) Using Catmentioning
confidence: 99%
See 1 more Smart Citation
“…Brivudine (BVDU) is an antiviral nucleoside analog used in the treatment of herpes zoster virus (HSV-1). Hervé et al in 2014 reported the synthesis of BVDU using a Pd-catalyzed Heck alkenylation reaction in 56% yield by using 10 mol% of Pd(OAc) 2 as a catalyst [52]. With a highly active catalytic system in hand, we explored the possibility of addressing the issues related to BVDU synthesis such as lower yields and the use of a high catalyst concentration.…”
Section: Synthesis Of Antiviral Drug Brivudine (Bvdu) Using Catmentioning
confidence: 99%
“…This effort led to the synthesis of 33 modified nucleosides using a single catalytic system with potential for further scale-up. alkenylation reaction in 56% yield by using 10 mol% of Pd(OAc)2 as a catalyst [52]. With a highly active catalytic system in hand, we explored the possibility of addressing the issues related to BVDU synthesis such as lower yields and the use of a high catalyst concentration.…”
Section: Suzuki-miyaura Cross Coupling On Four Natural Nucleosides Usmentioning
confidence: 99%
“…In 2014, for the first time, Len et al reported a palladium catalyzed Heck cross-coupling reaction between 5-iodo-2ʹ-deoxyuridine and various acrylate derivatives using ligand-free conditions and assisted-microwaves in pure water [20]. Those new conditions allowed a totally aqueous access to antiviral BVDU.…”
Section: Pd(ii)-catalyzed Heck Cross-coupling In H 2 Omentioning
confidence: 99%
“…The reaction of 5-iodo-2'-deoxyuridine (2) with various acrylate derivatives was carried out in the presence of Pd(OAc) 2 (Scheme 2.2) [3,4]. The use of task-specific ionic liquids (ILs) is also a "hot topic".…”
Section: Heck Reactionmentioning
confidence: 99%